Conceptualizing the Parliamentarization and Politicization of European Policies - Gheyle, Niels (2019)
In the past 20 years, two related literature strands have gradually moved centre stage of the attention of EU Studies scholars. The first is preoccupied with the ‘politicization of European integration’, a multi-faceted concept that aims to tie together a multitude of political and societal manifestations underlying an increasing controversiality of the EU. A second concerns the parliamentarization of the EU, referring to the changing (institutional) role and EU-related activities national parliaments engage in. The key point of this contribution is simple, but often overlooked: We can and should be seeing parliamentarization as a necessary, yet insufficient, component of a wider process of politicization. Doing so goes beyond the often ad hoc or pars pro toto theoretical assumptions in both literature strands, sheds new light on the normative consequences attached to these phenomena, and furthers a more complete understanding of how a ‘comprehensive’ politicization of European policies develops.